Comparison of the effects of neural therapy injection and extracorporeal shock wave therapy on pain and hand functions in the treatment of lateral epicondylitis: Comparison effects of injection and ESWT on epicondylitis - Dönmez , Ülkü; Aygün, Olgu (Journal of Surgery and Medicine, 2023)
Background/Aim: Lateral epicondylitis (LE), commonly known as “tennis elbow”, is a painful inflammatory condition affecting wrist extensor tendons. Various treatments, such as extracorporeal shockwave therapy (ESWT) and neural therapy injections, have been used to alleviate symptoms of LE. However, there is a limited number of comparative studies available. This study aims to compare the effectiveness of sequential neural therapy injections and ESWT in reducing pain and improving functionality in patients with LE. Methods: A retrospective cohort study analyzed data from 128 LE patients. Among them, 30 patients underwent neural therapy, while 30 underwent ESWT, following the exclusion criteria. Pain levels were measured using the visual analog scale (VAS), and functionality was assessed using the Duruöz hand index (DHI) before and after treatment. Results: Both neural therapy injections and ESWT led to substantial reductions in pain and improvements in functionality, with no notable differences observed between the two treatment methods. Additionally, no significant variations were found based on age, body mass index, gender, or the side of the elbow treated. Conclusion: The findings suggest that both neural therapy injections and ESWT are equally effective in managing symptoms of LE. Treatment choice may depend on patient preference, cost, availability, or other factors. Further research is necessary to examine long-term outcomes, potential side effects, and factors predicting a better response to one treatment.